A Validated Method for Quantification of Efavirenz in Dried Blood Spots Using High-Performance Liquid Chromatography–Mass Spectrometry. Issue 2 (April 2015) - Amara, Alieu B.; Else, Laura J.; Tjia, John; Olagunju, Adeniyi; Puls, Rebekah L.; Khoo, Saye; Back, David J.
Abstract : Background: Efavirenz (EFV) is one of the preferred components of first-line antiretroviral treatment. EFV is characterized by a long plasma half-life (40–55 hours) with large interpatient variability, which raises the potential for individualization of therapy. Analyses of EFV levels in plasma require specialized facilities (cold storage/transport) which, in resource-limited settings, can be problematic; dried blood spots (DBS)-EFV measurements thus provide a cheap easy alternative for therapeutic drug monitoring. Our aim was to develop and validate a liquid chromatography–mass spectrometry method to quantify EFV in DBS collected as part of clinical trials in resource-limited settings. Methods: DBS for standards, quality control samples, and patient samples were excised and then extracted with ethyl acetate/n-hexane (50/50 vol/vol) after addition of internal standard hexobarbital, and 1 mol/L K2 CO3 . The extract was evaporated to dryness, the residue reconstituted in mobile phase and analyzed directly by liquid chromatography–mass spectrometry. Gradient elution was on a reverse-phase C18 column using 1 mmol/L ammonium acetate in water and acetonitrile. Quantification was by selected reaction monitoring in negative ionization mode. DBS samples were obtained at several time points over 24 hours from HIV+ patients on either 400 or 600 mg EFV in combination with emtricitabine/tenofovir. Results: The internal standard and EFV eluted at 2.68 and 3.54 minutes, respectively in a 5-minute run time. Matrix effects were minimal (−5.4%). Calibration curves were validated over a concentration range of 25–5000 ng/mL. Intra-assay and interassay variations ranged between 6.7% and 8.7% for imprecision and 100.3% and 104.2% for accuracy. Mean recovery was >64%. The DBS data showed a strong positive correlation with a validated plasma EFV assay (R = 0.9764, P < 0.001). EFV concentrations from DBS were approximately 42% lower than the paired plasma values, and the ratio of blood/plasma did not change over the dosing interval. Conclusions: The validated assay is now routinely applied to clinical samples measuring DBS EFV for pharmacokinetic analysis. The methodology is robust, accurate, and sensitive.